The international role of the euro : a status report - Papaioannou, Elias; Porte, Richard; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
We survey the evidence on the international role of the euro a decade after its introduction. In the early nineties during the initial stages of Economic and Monetary Union, sceptics raised concerns that the single currency would lead to political disintegration and economic divergence. In contrast, some argued that the euro could become a major international currency within a relatively short time. In fact, the international importance of the single European currency is rising incrementally among a number of dimensions, and a 'middle-euro' scenario is emerging from the 'quasi-status-quo'. The share of the euro in foreign exchange reserves is rising, as is its usage in international trade. An increasing number of countries use the euro to anchor their currencies and issue their debt. The current global economic configuration of rising US inflation, a depreciating dollar, and the American trade and fiscal deficits reinforce the middle-euro scenario, in which the dollar and the euro share central roles in the international markets. Yet in the absence of a powerful shock, the ongoing adjustment is likely to occur gradually, rather than abruptly, and only if European policy makers continue financial market reforms and the European Central Bank maintains low inflation expectations.
Economic Papers